2022
DOI: 10.1177/09544100221101669
|View full text |Cite
|
Sign up to set email alerts
|

S-duct flow distortion with non-uniform inlet conditions

Abstract: Convoluted aero-engine intakes are often required to enable closer integration between engine and airframe. Although the majority of previous research focused on the distortion of S-duct intakes with undistorted inlet conditions, there is a need to investigate the impact of more challenging inlet conditions at which the intake duct is expected to operate. The impact of inlet vortices and total pressure profiles on the inherent unsteady flow distortion of an S-duct intake was assessed with stereo particle image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…1. This S-duct geometry was thoroughly investigated with experimental and computational studies [18,19], which include evaluation of steady and unsteady total pressure distortion [20], swirl distortion [9], sensitivity to inlet Mach number [17], as well as the effectiveness of passive and active flow control methods [21], and, more recently, the operation under non-uniform inlet conditions [11]. Downstream of the intake, a constant area duct provides optical access for measurements at the Aerodynamic Interface Plane (AIP), and a diffuser duct drives the flow to the suction fan (Fig.…”
Section: A Experimental Facility and S-duct Configurationmentioning
confidence: 99%
See 3 more Smart Citations
“…1. This S-duct geometry was thoroughly investigated with experimental and computational studies [18,19], which include evaluation of steady and unsteady total pressure distortion [20], swirl distortion [9], sensitivity to inlet Mach number [17], as well as the effectiveness of passive and active flow control methods [21], and, more recently, the operation under non-uniform inlet conditions [11]. Downstream of the intake, a constant area duct provides optical access for measurements at the Aerodynamic Interface Plane (AIP), and a diffuser duct drives the flow to the suction fan (Fig.…”
Section: A Experimental Facility and S-duct Configurationmentioning
confidence: 99%
“…2). Previous research demonstrated that AoA = -12° generates a vortex whose strength can alter the flow distortion characteristics at a noticeable level [11], thus this setup has been considered in the current study. Given the negative incidence of the delta wing with reference to the incoming flow, the vortex rotates anti-clockwise when viewed from downstream.…”
Section: B Inlet Vortex Generation Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…In [8], the influence of inlet conditions on the non-stationary aerodynamics of complex inlet devices by the method of a full-scale experiment was evaluated. That factor plays an important role in assessing the actual operation of the inlet device.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%